Pemahaman tentang Sakramen Pengurapan Orang Sakit dan Relevansinya terhadap Kesediaan untuk Menerimanya (Studi Kasus di RSUD dr. T. C. Hillers Maumere) - Bour, Eugenius Koresy; Jindung, Pilipus Benizi; Firman, Karifansius; Rosari, Yoseph Paulus de (SAPA - Jurnal Kateketik dan Pastoral, 2025)
This study aims to know, explain, and explore the understanding of the Catholic patients and their families at the Local Government Hospital (LGH) of dr. T. C. Hillers Maumere about the Sacrament of Anointing of the Sick (SAS) and its relevance to their willingness to receive the ministry of SAS for the patients. This study is a qualitative study with a case study approach. The data collection method uses observation, interview, and literature study techniques. The results of observation and interview show that Catholic patients and their families have a diverse understanding of SAS. These diverse understandings have relevance to their willingness to receive the ministry of SAS for patients. A good understanding of SAS will have a great effect on the willingness to receive the ministry of SAS for the patients or sick people who have begun to be in mortal danger. The pastoral step that can be taken is the teaching of the Catholics through catechesis and preaching.